Understanding Middle Neolithic food and farming in and around the Stonehenge World Heritage Site: An integrated approach. (August 2019) - Worley, Fay; Madgwick, Richard; Pelling, Ruth; Marshall, Peter; Evans, Jane A.; Lamb, Angela L.; López-Dóriga, Inés L.; Bronk Ramsey, Christopher; Dunbar, Elaine; Reimer, Paula; Vallender, John; Roberts, David
Abstract: Little synthesis of evidence for Middle Neolithic food and farming in Wiltshire, particularly in and around the Stonehenge World Heritage Site (WHS) has been possible, until now, due to a paucity of assemblages. The excavation of a cluster of five Middle Neolithic pits and an inhumation burial at West Amesbury Farm (WAF) has prompted a review of our understanding of pit sites of this period from the county. Bioarchaeological assemblages are used to investigate evidence for the consumption of animal and plant-based foods, and for agricultural and pastoral farming. For the first time Middle Neolithic zooarchaeological evidence, including strontium isotope data, is considered alongside archaeobotanical data, and radiocarbon dating. The absence of cultivated plants from WAF and contemporary sites in the county is consistent with the hypothesis that the reduction in cereal cultivation and greater reliance of wild plants witnessed in the later part of the Neolithic in southern England began in the Middle Neolithic. The zooarchaeological evidence from the same sites demonstrates that the shift away from cereal cultivation may be concurrent with, rather than earlier than, an increase in the relative proportion of deposited pig bones relative to cattle. Both cattle and pigs deposited in pits at WAF have strontium and sulphur isotope values consistent with the local biosphere, and therefore were potentially raised in the area. Zooarchaeological data from WAF compliments that from human dental calculus and lipid residues in associated Peterborough Ware pottery that local cattle husbandry included exploitation of dairy. It also highlights the presence of consistent food preparation methods between pits as seen through butchery practice. The faunal and archaeobotanical remains from contemporary pit deposits suggest that similar farming and subsistence strategies can be proposed across the county, though with some inter-site variation in deposition. Together these excavated pit sites are likely to represent only a sample of those present in the area. Application of a similar integrated approach to material from other Middle Neolithic pits holds potential for better understanding of food and farming in this previously neglected period. Highlights: Absence of cultivated plants from Middle Neolithic sites near Stonehenge Cereal grains present demonstrated to be intrusive through direct dating High proportion of pig (NISP) relative to cattle in Middle Neolithic pit sites Consistent butchery practice noted in pits at West Amesbury Farm Cattle and pig strontium values consistent with local biosphere